Pengaruh Pertumbuhan Laba, Leverage, dan Ukuran Perusahaan terhadap Kualitas Laba pada Perusahaan Indeks LQ45 yang Terdaftar di Bursa Efek Indonesia - Bomantara, Dandy Rajendra (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study examines the effects of earnings growth, leverage, and firm size on earnings quality in LQ45 Index companies listed on the Indonesia Stock Exchange during the 2018–2022 period. The study employs a quantitative approach using secondary data obtained from company financial statements. The sample was selected through purposive sampling and consisted of 20 companies, resulting in 100 firm-year observations. Data were analyzed using multiple linear regression with SPSS version 26. The results show that earnings growth has no significant effect on earnings quality, leverage has a negative and significant effect on earnings quality, and firm size has a positive and significant effect on earnings quality. Simultaneously, earnings growth, leverage, and firm size do not significantly affect earnings quality. The adjusted coefficient of determination is 5.3%, indicating that the three independent variables explain 5.3% of the variation in earnings quality, while the remaining 94.7% is explained by other factors outside the research model.